2003
DOI: 10.1179/037174503225011270
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical discrimination of newly discovered rare-metal bearing and barren pegmatites in the Pan-African (600 ± 150 Ma) basement of northern Nigeria

Abstract: This study reports some general field, petrographic and geochemical characteristics of the most notable of the newly discovered northern Nigerian pegmatites. The objective is to understand their setting and geochemical characteristics that can discriminate between rare-metal and barren pegmatites in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 18 publications
5
55
0
Order By: Relevance
“…This slight to sharp contrast in the values of some of the whole rock and eluvial soils for the alumina content of this study area in addition with other rare metal characteristics, confirms the complexity of the pegmatite type. These values are comparable to those observed for mineralized pegmatites of Nigeria, (Garba, 2003;Okunlola, 2005). (v) Albite type.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This slight to sharp contrast in the values of some of the whole rock and eluvial soils for the alumina content of this study area in addition with other rare metal characteristics, confirms the complexity of the pegmatite type. These values are comparable to those observed for mineralized pegmatites of Nigeria, (Garba, 2003;Okunlola, 2005). (v) Albite type.…”
Section: Resultssupporting
confidence: 87%
“…These have led to concentration of study on discrimination of the pegmatites into rare metal mineralized and barren ones in order to elucidate modes and features of mineralization (Matheis, 1981;Matheis et.al. 1982;Kuster, 1990;Garba, 2003). Recent studies by Okunlola, (2005) also defined the metallogeny of the rare metal Ta-Nb pegmatites of Nigeria outlining seven (7) broad fields namely Kabba-Isanlu, Ijero-Aramoko, Keffi-Nasarawa, Lema-Ndeji, Oke Ogun, Ibadan-Oshogbo and Kushaka-Birnin Gwari.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the rock ages showed that the pegmatities' emplacement in southwestern Nigeria occurred mainly after the peak of the Pan-African orogenic event in this area.The end of the Pan-African tectonic event is marked by a conjugate fracture system of the strike-slip faults (Ball, 1980). Gold and rare-metal pegmatites' mineralization is closely associated with the fractures in the Pan-African belt (Kuster, 1990;Ekweme and Matheis, 1995;Garba, 1992Garba, , 2003. The Ijero study area lies within latitudes 7 0 48' 36'' to 7 0 50' 06'' and longitudes 5 0 03' 54'' to 5 0 05' 42''.…”
Section: Local Geologymentioning
confidence: 99%
“…Central Nigeria is part of an Upper Proterozoic mobile belt extending from Algiers across the southern Sahara into Nigeria, Benin, and the Cameroun. This Pan-African belt continues into Northeast Brazil where analogous rare-metal mineralized pegmatites are also known [5,[9][10]. Bordered to the west by the West African Craton (stabilized around 2Ga) the Pan-African belt itself is made up of gneiss-migmatites, metasediments, and metavolcanics that have been subjected to polycyclic metamorphism and emplacement of igneous rocks.…”
Section: Introductionmentioning
confidence: 99%